51. PRECONCEPTION CARRIER SCREENING FOR MONOGENIC DISORDERS. (August 2019) - Shubina, J.; Sadelov, I.; Kochetkova, T.; Mukosey, I.; Goltsov, A.; Ekimov, A.; Donnikov, A.; Makarova, N.; Kalinina, E.; Veyukova, M.; Abubakirov, A.; Trofimov, D.
Abstract : Introduction: Up to 2% of newborn children have untreatable monogenic disorder. Preconception carrier screening is performed rarely. If a sperm donor is a carrier of mutation causing of frequent monogenic disorder probability of having a child with monogenic disorders raises dramatically. The aim of the study was to investigate frequency of monogenic disorder carrying for men who meet all requirements for being sperm donors. Material & methods: DNA from sperm samples was extracted using New iGENatal kit. Whole exome sequencing of 25 samples was performed using Ion S5 sequencers and Ion AmpliSeq Exome RDY Kit. Read mapping and variant calling was performed using Torrent Suite software. Variant annotation was performed with Variant effect predictor tool. Results & Conclusions: 15 men (60%) were carriers of at least 1 pathogenic mutation associated with an autosomal recessive disorder. 6 (24%) were carriers of a disorder with population carrier frequency 1/250 and higher. With no tests for second parent the probability of having a child with a monogenic disorder is higher than 1/1000. This result demonstrates the importance of preconception carrier screening, particularly in IVF programs using donor sperm. The study is supported by the Ministry of Healthcare of Russian Federation